Sulfanyl Radical Addition to Alkynes: Revisiting an Old Reaction to Enter the Novel Realms of Green Chemistry, Bioconjugation, and Material Chemistry - Monesi, Alessandro <1983> (Alma Mater Studiorum - Università di Bologna, 2012)
In the last decade considerable attention has been devoted to the rewarding use of Green Chemistry in various synthetic processes and applications. Green Chemistry is of special interest in the synthesis of expensive pharmaceutical products, where suitable adoption of “green” reagents and conditions is highly desirable. Our project especially focused in a search for new green radical processes which might also find useful applications in the industry. In particular, we have explored the possible adoption of green solvents in radical Thiol-Ene and Thiol-Yne coupling reactions, which to date have been normally performed in “ordinary” organic solvents such as benzene and toluene, with the primary aim of applying those coupling reactions to the construction of biological substrates. We have additionally tuned adequate reaction conditions which might enable achievement of highly functionalised materials and/or complex bioconjugation via homo/heterosequence. Furthermore, we have performed suitable theoretical studies to gain useful chemical information concerning mechanistic implications of the use of green solvents in the radical Thiol-Yne coupling reactions.